Isolation and identification of Enterococcus faecalis membrane proteins using membrane shaving, 1D SDS/PAGE, and mass spectrometry. Issue 6 (19th May 2016) - Cathro, Peter; McCarthy, Peter; Hoffmann, Peter; Zilm, Peter
Abstract : Enterococcus faecalis is a significant nosocomial pathogen, which is able to survive in diverse environments and resist killing with antimicrobial therapies. The expression of cell membrane proteins play an important role in how bacteria respond to environmental stress. As such, the capacity to identify and study membrane protein expression is critical to our understanding of how specific proteins influence bacterial survival. Here, we describe a combined approach to identify membrane proteins of E. faecalis ATCC V583 using membranes fractionated by either 1D SDS/PAGE or membrane shaving, coupled with LC‐ESI mass spectrometry. We identified 222 membrane‐associated proteins, which represent approximately 24% of the predicted membrane‐associated proteome: 170 were isolated using 1D SDS/PAGE and 68 with membrane shaving, with 36 proteins being common to both the techniques. Of the proteins identified by membrane shaving, 97% were membrane‐associated with the majority being integral membrane proteins (89%). Most of the proteins identified with known physiology are involved with transportation across the membrane. The combined 1D SDS/PAGE and membrane shaving approach has produced the greatest number of membrane proteins identified from E. faecalis to date. These protocols will aid future researchers investigating changes in the membrane proteome of E. faecalis by improving our understanding of how E. faecalis adapts and responds to its environment. Abstract : The study of membrane protein expression is critical to our understanding of how specific proteins influence bacterial survival. We describe a combined approach to identify membrane proteins of E. faecalis V583 using membranes fractionated by either 1D SDS/PAGE or membrane shaving, coupled with LC‐ESI mass spectrometry. This approach has produced the greatest number of membrane proteins identified from E. faecalis to date.